Between Neoliberalism and Nationalist Populism: What Role for the 'European Social Model' and Social Quality in Post-Brexit Europe?. Issue 1 (27th January 2019) - Corbett, Steve; Walker, Alan
Abstract : This article investigates the idea of 'the social' in Europe after the UK's EU Referendum vote, with reference to the 'European social model'. It is argued that the key drivers of the vote outcome did not feature in the referendum campaign but are features of longer running and deeper fractures in both British and wider European society. Especially, the lack of response to societal problems, the downplaying of individual participation, and a crisis in democracy created by an increasingly neoliberal direction within an EU concerned with austerity and social control, contrary to the values of the 'European social model' (Walker, 2005). In the absence of action for better 'social quality', this overall neoliberal direction has also weakened the progressive and integrative potential of social policy. The result is the regressive nationalist populist backlash against neoliberal technocracy. Instead, we argue that answers to contemporary European challenges must focus on improving social quality and democracy.